Rancang Bangun Aplikasi Monitoring Kegiatan Tanggap Darurat Bencana Di Kota Surabaya - Utama, Setya Hadi; Lusiani, Titik; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Palang Merah Indonesia (PMI) is an organization of national associations in Indonesia which is engaged in social humanity, one of the services performed by the PMI is a disaster handling. In the event of a disaster, the Red Cross Indonesia will dispatch a team named SATGANA. Teams that has been dispatched must make a report on the disaster that has occurred. Right now in PMI Surabaya, SATGANA team is not well monitored, the letter of assignment is often too late to be given, and the assessment should be reported at least 30 minutes after arriving at the site, often delayed or even not given. Another problem that arises is the absence of a system that provides information to PMI regarding status of each report is written, it is not stored properly, so many reports were missing or damaged. Based on the above problems, it takes an application that is able to facilitate the process of monitoring for the PMI. It also needed a system that helps the PMI for making the reports of the disaster. Developed systems made using the Waterfall method. Based on the results of trials that have been done, the system can meet the needs of the PMI Surabaya City in the process of disaster news, monitoring and process team SATGANA disaster reports.